Sondeos de Opinion -El Fracaso del Oráculo- - Colomé, Gabriel (La Sociología en sus Escenarios, 2010)
Abstract. Unlike the rest of the western democracies, Spain structures its political system and consolidates its system by means of the implantation of the democratic system with mass media of modern masses, mainly, the television. This element is decisive in the construction of the political parties of masses with tendencies catch-all, with leaderships and personalization of the electoral campaigns. These distinguishing characteristics mark the Spanish system of political organizations. Resumen. A diferencia del resto de las democracias occidentales, España estructura su sistema político y consolida su sistema por medio de la implantación del sistema democrático con unos medios de comunicación de masas modernos, sobre todo, la televisión. Este elemento es decisivo en la construcción de los partidos políticos de masas con tendencias catch-all, con liderazgos y personalización de las campañas electorales. Estos rasgos distintivos marcan el sistema de partidos español. <!--[if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-520092929 1073786111 9 0 415 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:10.0pt; margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} .MsoPapDefault {mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;} @page WordSection1 {size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0;} div.WordSection1 {page:WordSection1;} --> <!--[if gte mso 10]> <![endif]-->